BAHASA DAN KELAHIRANNYA - Ening Herniti (Adabiyyāt: Jurnal Bahasa dan Sastra, 2010)
Language is a unique trait, which differentiates human being from other creatures. Language ability is a human nature whereas other creatures share their communication system. A study on chimpanzee proves that language only works on human. The study depicts that language is a one of the most primary characteristics of human nature. Chomsky calls it as language acquisition tool.  Philosophical and scientific speculation on the function of language in man was frequent throughout history, dating back to the age of Plato and Aristotle. Yet those speculations have been approached more often by scientists than philosophers. Many theories propose that the gains to be had from language and/or reason were probably mainly in the area of increasingly sophisticated social structures.